APOE Genotype Differentially Modulates Effects of Anti-Aβ, Passive Immunization in APP Transgenic Mice. Issue 1 (December 2017) - Pankiewicz, Joanna; Baquero-Buitrago, Jairo; Sanchez, Sandrine; Lopez-Contreras, Jennifer; Kim, Jungsu; Sullivan, Patrick; Holtzman, David; Sadowski, Martin
Abstract Background APOE genotype is the foremost genetic factor modulating β-amyloid (Aβ) deposition and risk of sporadic Alzheimer's disease (AD). Here we investigated howAPOE genotype influences response to anti-Aβ immunotherapy. Methods APPSW /PS1dE9 (APP) transgenic mice with targeted replacement of the murineApoe gene for humanAPOE alleles received 10D5 anti-Aβ or TY11-15 isotype control antibodies between the ages of 12 and 15 months. Results Anti-Aβ immunization decreased both the load of fibrillar plaques and the load of Aβ immunopositive plaques in mice of allAPOE backgrounds. Although the relative reduction in parenchymal Aβ plaque load was comparable across allAPOE genotypes, APP/ε4 mice showed the greatest reduction in the absolute Aβ plaque load values, given their highest baseline. The immunization stimulated phagocytic activation of microglia, which magnitude adjusted for the post-treatment plaque load was the greatest in APP/ε4 mice implying association between the ε4 allele and impaired Aβ phagocytosis. Perivascular hemosiderin deposits reflecting ensued microhemorrhages were associated with vascular Aβ (VAβ) and ubiquitously present in control mice of allAPOE genotypes, although in APP/ε3 mice their incidence was the lowest. Anti-Aβ immunization significantly reduced VAβ burden but increased the number of hemosiderin deposits across allAPOE genotypes with the strongest and the weakest effect in APP/ε2 and APP/ε3 mice, respectively. Conclusions Our studies indicate thatAPOE genotype differentially modulates microglia activation and Aβ plaque load reduction during anti-Aβ immunotherapy. TheAPOE ε3 allele shows strong protective effect against immunotherapy associated microhemorrhages; while, conversely, theAPOE ε2 allele increases risk thereof.